Eighteen-hour inhibitory effect of s-ketamine on potassium- and ischemia-induced spreading depolarizations in the gyrencephalic swine brain - Sánchez-Porras, Renán; Kentar, Modar; Zerelles, Roland; Geyer, Martina; Trenado Colin, Carlos Alberto; Hartings, Jed A.; Woitzik, Johannes; Dreier, Jens P.; Santos, Edgar (Neuropharmacology, 2022)
Spreading depolarizations (SDs) are characterized by near-complete breakdown of the transmembrane ion gradients, cytotoxic edema, and glutamate release. SDs are associated with poor neurological outcomes in cerebrovascular diseases and brain trauma. Ketamine, a N-methyl-d-aspartate receptor antagonist, has shown to inhibit SDs in animal models and in humans. However, little is known about its SD-inhibitory effect during long-term administration. Lissencephalic animal models have shown that ketamine loses its SD-blocking effect after some minutes to hours. Physio-anatomical differences between lissencephalic and the more evolved gyrencephalic animals may affect their SDs-blocking effect. Therefore, information from the last may have more translational potential. Therefore, the aim of this study was to investigate the 18 h-effect of s-ketamine as a basis for its possible long-term clinical use for neuroprotection. For this purpose, two gyrencephalic swine brain models were used. In one, SDs were elicited through topical application of KCl; in the other model, SDs were spontaneously induced after occlusion of the middle cerebral artery. S-ketamine was administered at therapeutic human doses, 2, 4 and 5 mg/kg BW/h for up to 18 h. Our findings indicate that s-ketamine significantly reduces SD incidence and expansion without clear evidence of loss of its efficacy. Pharmacological susceptibility of SDs to s-ketamine in both the ischemic gyrencephalic brain and well-perfused brain was observed. SDs were most potently inhibited by s-ketamine doses that are above the clinically recommended (4 mg/kg BW/h and 5 mg/kg BW/h). Nonetheless, such doses are given by neurointensivists in individual cases. Our results give momentum to further investigate the feasibility of a multicenter, neuromonitoring-guided, proof-of-concept clinical trial.